Working Toward Integrative Health Equity: Reflections from Acupuncture Implementation Within a Pediatric Primary Care Safety-Net Clinic - Jenifer Matthews; Karen Villanueva; Susan Yee; Ariana Thompson-Lastad (Mary Ann Liebert, 2022)
Complementary and integrative health (CIH) care is well positioned to provide culturally affirming, patient-centered, and evidence-informed care for vulnerable children and families. Our pediatric primary care clinic has responded to the growing evidence base for CIH in pediatrics and the multiple national calls to action to include nonpharmacologic approaches in the treatment of pain by implementing acupuncture.1,2 Our clinic, a Federally Qualified Health Center (FQHC) in Oakland, CA, USA, serves a multiracial low-income pediatric patient population with 91% of the patients insured by Medicaid. Families served by this clinic face high levels of community trauma and structural violence, contributing to high prevalence of anxiety, depression, post-traumatic stress disorder, and chronic and acute pain conditions.3,4 Within the current biomedical paradigm, treatment options often include pharmaceuticals, lifestyle recommendations, and mental health referrals, but access to these can be fragmented and frustrating for both patients and providers alike. In their call to action, ?Integrative Medicine and the Imperative for Health Justice,? authors Chao and Adler urge us to ?leverage integrative medicine to advance health equity, that is, the attainment of the highest level of health for all people.?5 Acupuncture is one form of CIH that has a growing evidence base for use among children. There is strong interest in the use of pediatric acupuncture in the United States, with evidence for the safety and feasibility of pediatric and adolescent acupuncture as well as acceptability of acupuncture by children.6,7 The benefits of acupuncture for children have been documented in children experiencing chronic pain chemotherapy-associated symptoms, and anxiety, among other conditions.8?10 Widespread implementation of acupuncture has been limited for multiple reasons, including limited or nonexistent insurance reimbursement as well as assumptions that children will be fearful of needles. The term ?acutherapy? was introduced in the clinic to encompass acupuncture, acupressure, and Gua Sha. This term was used due to concern about patients? reactions and negative conditioning to the term ?puncture? and the potential association of an acupuncture needle and treatment being similar to puncture with a hypodermic needle for venipuncture or vaccine administration. Pediatric patients and their families, particularly those who are unfamiliar with this form of care, can be wary when they hear the words, ?puncture? or ?needles,? and language matters with all patients, especially those who have a history of chronic illness or medical trauma. As part of a larger hospital-based interdisciplinary Integrative Medicine Medical Staff Committee, the group?including a physician, licensed acupuncturist/nurse, social worker, and sociologist?collected preliminary data to better understand staff and family priorities, as well as potential barriers to care as acutherapy was implemented in this clinic. Although there are exemplary models of pediatric integrative medicine implementation, these programs are often in academic hospital-based inpatient settings and it can be difficult to translate these experiences to a pediatric primary care safety-net setting.11?13 However, Silver Highfield et al. found that by reducing barriers to access, both pediatric and adult patients in a similar safety-net urban setting utilized acupuncture as part of ongoing primary care.14 To reduce barriers and center family voices in the planning stage of this project, caregivers were surveyed about their current CIH usage and interest, and offered caregiver engagement sessions in multiple languages in the clinic. Over a 3-month period in 2019?2020, families were surveyed in three languages?English, Spanish, and Arabic?about current CIH usage and potential interest in CIH modalities if offered in the clinic, as well as ways to make CIH offerings convenient and accessible. Fifty-nine caregivers completed the survey, and included families broadly reflective of the patients served in clinic* (Table 1). Table 1. Caregiver Demographics Primary languagea, % (n) ?English 76 (45) ?Spanish 24 (14) ?Arabic 5 (3) ?Tigrinya 2 (1) ?Other 5 (3) Insuranceb, % (n) ?Medicaid 88 (52) ?Private insurance 12 (7) ?No insurance 0 (0) Ethnicitiesc, % (n) ?African American or Black 39 (23) ?Latino/Hispanic 32 (19) ?White/Caucasian 17 (10) ?Asian 12 (7) ?Other 12 (7) ?Native American/ 3 (2) ?American Indian ?Pacific Islander/Samoan/Native Hawaiian 2 (1) Children's ages (years)d, % (n) ?0?2 29 (17) ?2?5 41 (24) ?6?11 46 (27) ?12?18 30 (18) ?>18 5 (3) Survey participants could select multiple response options as applicable to their identities and situations aSurvey question: What are the primary languages you speak at home? bSurvey question: What kind of insurance does your child(ren) have? cSurvey question: What is your race or ethnicity? (Check all that apply.) dSurvey question: How old are your children? (Check all that apply.) English (76%), Spanish (24%), and Arabic (5%) were the primary languages spoken at home. Most caregivers identified Medicaid (88%) as their child's insurance and self-identified as African American or Black (39%), Latino/Hispanic (32%), or White/Caucasian (17%). Almost one-fourth of children were identified by their caregivers to have a chronic illness. Of the 59 caregivers surveyed, over half (53%) had used CIH approaches for their children for a wide range of health conditions, most commonly anxiety/stress (29%), pain (28%), and asthma or allergies (26%). The most common forms of CIH used by families were herbal medicine/supplements (29%), mindfulness/meditation/relaxation or breathing practices (27%), yoga/Tai Chi/qigong (15%), and exercise and nutrition coaching (15%). Over half of families were interested in CIH being offered in the primary care clinic with exercise and nutrition coaching (58%), mindfulness/meditation, relaxation and breathing training (51%), and acutherapy (47%) as the top three priorities. When asked specifically about making acutherapy accessible for their children, most caregivers indicated that this clinic should work to make the service free or covered by insurance (82%) as well as making sure clinic staff were informed and knowledgeable about CIH (52%). In addition, informal engagement sessions were offered for caregivers who completed the survey to learn more about integrative health modalities and to share what resources and practices they use. These sessions were hosted to create a space to affirm families? healing practices and gather input into clinic design and offerings. Notes on caregivers? comments were taken in each session. Caregivers? perspectives on CIH focused on four areas: 1.Interest in increasing personal understanding of CIH, specifically access to research findings about CIH modalities and how they work with conventional medicine. 2.Desire for CIH implementation and trainings in the clinic, including approaches that would affirm and include families? existing cultural and spiritual healing practices. One African American participant initially stated, ?I don't have any cultural practices. Those were lost,? then realized after looking at other parents? practices, that she, too, had healing practices that had been shared with her by her grandmother and mother. 3.Emphasis on the need for CIH to be accessible to all patients, by ensuring well-trained staff, coordinated care, low-cost or no-cost services, and expanded hours. 4.Shared perspective on CIH as an opportunity to create a more collaborative and less hierarchical approach to primary care. Caregivers suggested that CIH implementation might make care more collaborative and that this could promote healing and understanding between families and staff. Building on this information, acutherapy began being offered at no cost to clinic patients in January 2020 through a shared-visit model, where patients were seen by both a physician and a licensed acupuncturist with the physician billing for the visit. The licensed acupuncturist's time was paid for through a hospital-based innovation grant. The COVID-19 pandemic required this clinic to discontinue all nonurgent in-person visits after seven acupuncture clinic sessions. In-person acutherapy visits resumed in Fall 2020.